A Prospective Multi-Institutional Evaluation of Iatrogenic Urethral Catheterization Injuries. Issue 10 (3rd October 2022) - Croghan, Stefanie M.; Hayes, Leah; O'Connor, Eabhann M.; Rochester, Mark; Finch, William; Carrie, Anne; Considine, Shane W.; D'Arcy, Frank; Riogh, Aisling Nic an; Mahmalji, Wasim; Elhadi, Mohammed; Thursby, Helen; et al.
Abstract: Objectives: To perform a multi-institutional investigation of incidence and outcomes of urethral trauma sustained during attempted catheterization. Patients & Methods: A prospective, multi-center study was conducted over a designated 3-4 month period, incorporating seven academic hospitals across the UK and Ireland. Cases of urethral trauma arising from attempted catheterization were recorded. Variables included sites of injury, management strategies and short-term clinical outcomes. The catheterization injury rate was calculated based on the estimated total number of catheterizations occurring in each center per month. Anonymised data were collated, evaluated and described. Results: Sixty-six urethral catheterization injuries were identified (7 centers; mean 3.43 months). The mean injury rate was 6.2 ± 3.8 per 1000 catheterizations (3.18–14.42/1000). All injured patients were male, mean age 76.1 ± 13.1 years. Urethral catheterization injuries occurred in multiple hospital/community settings, most commonly Emergency Departments (36%) and medical/surgical wards (30%). Urological intervention was required in 94.7% (54/57), with suprapubic catheterization required in 12.3% (n = 7). More than half of patients (55.56%) were discharged with an urethral catheter, fully or partially attributable to the urethral catheter injury. At least one further healthcare encounter on account of the injury was required for 90% of patients post-discharge. Conclusions: This is the largest study of its kind and confirms that iatrogenic urethral trauma is a recurring medical error seen universally across institutions, healthcare systems and countries. In addition, urethral catheter injury results in significant patient morbidity with a substantial financial burden to healthcare services. Future innovation to improve the safety of urinary catheterization is warranted.